2020
DOI: 10.1109/ted.2020.3025846
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Imprint in FE-HfO₂ and Its Recovery

Abstract: Ferroelectric (FE)-HfO2 based FETs (FEFETs) are one of the most promising candidates for emerging memories. However, the FE material suffers from a unique reliability phenomenon known as imprint: the coercive voltage shifts during data retention, which has been regarded as a major issue for memory operation, while the mechanism causing it is still under research. In this paper, imprint and its recovery in FE-HfO2 are investigated in detail by comprehensive electrical measurements to reveal its underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…This is believed to result from the commencement of the positive (stress and relaxation) voltage-induced polarisation of the FE layer to the low Vt state, and hence the lower Vt value. That this process can take place at these low voltages (for Vstress ~ 1.5V, Vrelax ~0.5V), after long (stress and relaxation) times is consistent with results on the time and bias dependence of polarisation [4]. This effect is more pronounced at lower temperatures, also in agreement with a recent report suggesting increased orthorhombic phase in Si-doped HfO2 on reducing temperature [6].…”
Section: Conventionalsupporting
confidence: 92%
See 2 more Smart Citations
“…This is believed to result from the commencement of the positive (stress and relaxation) voltage-induced polarisation of the FE layer to the low Vt state, and hence the lower Vt value. That this process can take place at these low voltages (for Vstress ~ 1.5V, Vrelax ~0.5V), after long (stress and relaxation) times is consistent with results on the time and bias dependence of polarisation [4]. This effect is more pronounced at lower temperatures, also in agreement with a recent report suggesting increased orthorhombic phase in Si-doped HfO2 on reducing temperature [6].…”
Section: Conventionalsupporting
confidence: 92%
“…At such physical thickness, the presence (and absolute number) of defects give rise to capture and emission of electrons injected in the FE-layer, which also modulate the device performance. The combination of this defectdominated behaviour together with the ferroelectric polarisation presents quite a challenge for device operation and reliability engineering [4] and is the objective of this work. We elucidate the energy distributions of oxide defect states in Si doped-HfO2 for FE-RAM applications using multiple defect modelling techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5–11 ] However, there are still reliability issues for practical use, including insufficient switching endurance [ 12,13 ] and fatigue properties. [ 14–16 ] In the case of HfO 2 ‐based ferroelectric thin films, their large time‐dependent imprint [ 17–22 ] and wake‐up effect [ 16,17,23–27 ] —which distinguish them from conventional ferroelectric materials—play important roles in understanding these critical issues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that the imprint effect in a HfO 2 ‐based ferroelectric capacitor occurs during polarization retention, even at room temperature. [ 17–19,21,22 ] The time‐dependent imprint also occurs in ferroelectric‐gate field effect transistors. [ 20 ] Zacharaki et al.…”
Section: Introductionmentioning
confidence: 99%